2014
DOI: 10.1007/s00381-014-2366-y
|View full text |Cite
|
Sign up to set email alerts
|

Surgical and clinical aspects of cerebellar pilomyxoid-spectrum astrocytomas in children

Abstract: Cerebellar PMSAs express an aggressive clinical behavior and impose more operative challenges than PAs. These tumors may represent a clinical spectrum-at its benign end lies PA, while PMA lies at the aggressive end, with IPA lying just behind. Such concepts could be used to guide management in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 13 publications
0
14
1
Order By: Relevance
“…Information about PMA of the cerebellum is very little due to the very few reported cases. Only 10 cases of PMA in the cerebellum have been reported [ 5 9 ]. Although the prognosis of cerebellar PMA remains unknown, several authors have reported a more favorable outcome for cerebellar PMA than for PMA of other locations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Information about PMA of the cerebellum is very little due to the very few reported cases. Only 10 cases of PMA in the cerebellum have been reported [ 5 9 ]. Although the prognosis of cerebellar PMA remains unknown, several authors have reported a more favorable outcome for cerebellar PMA than for PMA of other locations.…”
Section: Discussionmentioning
confidence: 99%
“…This is because GTR or near total resection is more feasible for cerebellar PMA [ 5 7 10 ]. El Beltagy and his colleagues [ 9 ] reported a recurrence rate of 66.7%, GTR rate of 8.3%, and LD of 75% in PMA of the cerebellum. The 5-year overall survival rate was 87.5%; however, this was observed in a combination of PMA and IPT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A fascinating aspect that links PMA with PA is the observation of maturation from PMA to intermediate PMA, or even PA, on subsequent surgeries in occasional reported cases (3, 4, 5, 8, 11) and the existence of intermediate forms (12). In the original description of PMA, no maturation occurred in two of two recurrent tumors (27), but in the study by Johnson et al of intermediate PMAs there were 9 examples of recurrences and tendency to maturation was quite variable (12).…”
Section: Discussionmentioning
confidence: 99%
“…Although we did not specifically review of the extent of surgical resection in our cohort, Komotar et al in their larger series of 42 PAs and 21 PMAs restricted to hypothalamic/chiasm, felt that “the extent of resection was comparable in the PMA and PA groups and did not affect the observed differences in PFS and OFS” (15). The greater extent of invasion of adjacent tissues in PMAs versus PAs may, however, lead to greater ability to achieve gross total resection (GTR) in other anatomical sites such as cerebellum (18), where GTR could be achieved in 90.9% of cerebellar PAs versus 13.6% of PMAs (8). Two PMA patients in our series had CSF dissemination (cases 2 and 4, one with autopsy documentation, see Table 1), which is generally, but not invariably (26), unresponsive to therapies.…”
Section: Discussionmentioning
confidence: 99%